Buildability Factors That Influence Micro-level Formwork Labour Productivity Of Beams In Building Floors - Jarkas, Abdulaziz M. (Penerbit Universiti Sains Malaysia, 2011)
Buildability is one of the most important factors that influence labour productivity. Nevertheless, a thorough literature examination revealed a dearth of research concerning the effects of buildability on labour productivity of in situ reinforced concrete construction. Beams are major components of building floors, and the objective of this investigation is to explore the buildability factors that influence their micro-level formwork labour productivity. Therefore, a large volume of productivity data was collected and analysed using a categorical interaction-regression method. As a result, the main and interaction effects of beam repetition, size, intersections and span geometry were determined. The obtained results indicate that the investigated factors significantly influence the forming operation labour efficiency and substantiate the importance of applying design rationalisation, standardisation and repetition concepts to the design stage of construction projects. The findings satisfy the explored activity buildability knowledge gap, which can be used to provide designers with feedback on how well their designs consider the buildability principle requirements, as well as their decision consequences on the forming operation productivity.